2007
DOI: 10.1109/jproc.2007.896511
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Detection for Channels With Memory

Abstract: By examining various approaches and techniques, this paper aims to help designers to create improved algorithms for communications over noisy channels with memory.By Achilleas Anastasopoulos, Member IEEE, Keith M. Chugg, Member IEEE, Giulio Colavolpe, Member IEEE, Gianluigi Ferrari, Member IEEE, and Riccardo Raheli, Member IEEE ABSTRACT | In this paper, we present an overview on the design of algorithms for iterative detection over channels with memory. The starting point for all the algorithms is the implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…Essentially, FGs represent graphically the factorization of a function, and have been shown to be a good alternative to solve complex inference problems. Many recent articles address the use of FG-based algorithms (also known as belief propagation (BP) algorithms) for detection or equalization in channels with memory [31][32][33]. Recently, this framework has been extended to ICI channels: a set of detection algorithms have been presented based on the Ungerboeck approach for MAP symbol detection [34], while in [35], progressive parallel ICI cancelation has been proposed based on FGs.…”
Section: Background On Ici Suppressingmentioning
confidence: 99%
“…Essentially, FGs represent graphically the factorization of a function, and have been shown to be a good alternative to solve complex inference problems. Many recent articles address the use of FG-based algorithms (also known as belief propagation (BP) algorithms) for detection or equalization in channels with memory [31][32][33]. Recently, this framework has been extended to ICI channels: a set of detection algorithms have been presented based on the Ungerboeck approach for MAP symbol detection [34], while in [35], progressive parallel ICI cancelation has been proposed based on FGs.…”
Section: Background On Ici Suppressingmentioning
confidence: 99%
“…For fixed-lag MAP symbol estimation, Zhang, Fitz, and Gelfand [ZFG97] proposed to use per-survivor Kalman filtering, echoing earlier work by Iltis et al [ISG94]. Anastasopoulos and Chugg [AC00] then presented two general families of trellis algorithms, one based on parameter-first combining and the other on sequence-first combining, that yield both forward-backward and fixed-lag algorithms.…”
Section: Near-optimal Trellis-psp Equalization For Single-carrier Schmentioning
confidence: 99%
“…For example, Kubo, Murakami, and Fujino [KMF94] proposed to use the Viterbi algorithm in conjunction with the LMS algorithm [Hay01] for per-survivor channel estimation, whereas Raheli, Polydoros, and Tzou [RPT95] proposed to use the Viterbi algorithm in conjunction with the RLS algorithm [Hay01]. Other LMS and RLS approaches were discussed in [AC00].…”
Section: Reduced-complexity Trellis-psp Equalization For Single-carrimentioning
confidence: 99%
“…These methods iteratively update the extrinsic information between soft equalizer and soft decoder where the output of each terminal is striped off the input information. An extensive review of these methods can be found in [3].…”
Section: Introductionmentioning
confidence: 99%